Determining the development stage of the ossification centers around the elbow may aid in deciding whether to use ESIN or not in adolescents' forearm shaft fractures. (4th July 2021) - Stöckell, Markus; Pokka, Tytti; Lutz, Nicolas; Sinikumpu, Juha-Jaakko
Abstract : Background and purpose — Elastic stable intramedullary nailing (ESIN) is the preferred method of operative stabilization of unstable pediatric forearm shaft fractures. However, the decision whether to use ESIN or open reduction and internal fixation (ORIF) in older children or teenagers is not always straightforward. We hypothesized that the development stage of the elbow would aid in evaluating the eligibility of the patient for ESIN. Patients and methods — All eligible children, aged <16 years who were treated with ESIN in Oulu University Hospital, during 2010–2019 were included (N = 70). The development stages of 4 ossification centers were assessed according to the Sauvegrain and Diméglio scoring. The proportion of impaired union vs. union was analyzed according to bone maturity, by using the optimal cutoff-points determined with receiver operating characteristics (ROC). Results — Development stage ≥ 6 in the olecranon was associated with impaired union in 20% of patients, compared with none in stages 1–5 (95% CI of difference 8% to 24%). Trochlear ossification center ≥ 4 was associated with impaired union in 17% of patients (CI of difference 7% to 36%) and lateral condyle ≥ 6 in 13% of patients (CI of difference 3.4% to 30%). Proximal radial head ≥ 5.5 was associated with impaired union in 18% of patients (CI of difference 7% to 39%). Interpretation — Recognizing the rectangular or fused olecranon ossification center, referring to stage ≥ 6, was in particular associated with impaired fracture healing. This finding may aid clinicians to consider between ESIN and plating, when treating forearm shaft fracture of an older child or teenager.